Impedimetry and microscopy of electrosynthetic poly(propylene thiophenoimine)-co-poly(3,4 ethylene dioxythiophene) dendritic star copolymer - Olowu, Rasaq A; Williams, Avril; Ndangili, Peter M.; Ngece, Rachel F; Mailu, Stephen N; Baker, Priscilla; Iwuoha, Emmanuel (My University, 2011)
The electrochemical impedance spectroscopy of generation 2 poly(propylene thiophenoimine)-co-poly(3,4 ethylene dioxythiophene) dendritic star copolymer (G2PPT-co-PEDOT) film was studied in LiClO4 solution. The results show that the electrochemical deposition of G2PPT-co-PEDOT on gold electrode decreased the electrochemical charge transfer resistance when compared to Au|PEDOT|LiClO4 and Au|LiClO4 interfaces. This is attributed to an increase in the conjugation length of the polymer as result of the linking of the highly conjugated PEDOT to the dendrimer. Bode impedimetric analysis indicates that G2PPT-co-PEDOT is a semiconductor with a maximum phase angle shift of 67.5° at 100 mHz. The star copolymer exhibited a 2-electron electrochemistry and a surface coverage of 97.3%. The morphology of the dendritic star copolymer was investigated by scanning electron microscopy and atomic force microscopy
Keywords: Electrochemical impedance spectroscopy; Conducting polymer; Atomic force microscopy; Scanning electron microscopy; Dendritic star copolymer; Nanomaterials; PEDOT